2001
DOI: 10.1159/000050173
|View full text |Cite
|
Sign up to set email alerts
|

Locally Recurrent Rectal Cancer

Abstract: Local recurrence (LR) varies from less than 4% to greater than 50%; several tumor factors and operative techniques may influence rate of LR. Of greatest interest has been the considerable inter-surgeon variation, even within the same institution. An LR rate of less than 10% has been consistently reported by those who use total mesorectal excision even without any form of adjuvant therapy, either preoperatively or postoperatively. These findings raise important questions about surgical technique, subspecialty t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Since total mesorectal excision was adopted as the standard treatment of patients with rectal carcinoma, improvements have been made in decreasing its local recurrence and prolonging survival of patients [1][2][3][4][5][6][7][8] . However, even having undergone radical resection with total mesorectal excision, about 5%-40% of patients with rectal carcinoma have local recurrence [9][10][11][12][13][14] . The survival of patients with advanced low rectal cancer www.wjgnet.com still remains poor.…”
Section: Introductionmentioning
confidence: 99%
“…Since total mesorectal excision was adopted as the standard treatment of patients with rectal carcinoma, improvements have been made in decreasing its local recurrence and prolonging survival of patients [1][2][3][4][5][6][7][8] . However, even having undergone radical resection with total mesorectal excision, about 5%-40% of patients with rectal carcinoma have local recurrence [9][10][11][12][13][14] . The survival of patients with advanced low rectal cancer www.wjgnet.com still remains poor.…”
Section: Introductionmentioning
confidence: 99%
“…Local recurrence of middle and lower rectal carcinoma after curative resection has significant morbidity and mortality [4,[12][13][14][15] and its recurrence rate varies from less than 4% to greater than 50%. Since TME was adopted as the standard treatment of patients with rectal carcinoma, a significant decrease in local recurrence and a trend to improve relative survival have been reported [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…However, local recurrence of rectal carcinoma occurs in about 4%-50% of patients even after radical resection of primary tumors and lymph nodes [4][5][6][7][8] . The risk factors for local recurrence of rectal carcinoma remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicated that the local recurrence rate of rectal carcinoma after simple radical resection was 4% to 40% [1]. The survival period of patients with untreated postoperative local recurrence is generally 3.5 to 13 months [2].…”
Section: Introductionmentioning
confidence: 99%